“This Garden, London’s Arcadian Dream". Juliusz Słowacki and St. James’s Park Against the Backdrop of the Cultural History of the City Park - Leszczyński, Marcin (Porównania, 2024)
The essay explores the relationship between nineteenth-century urban parks in London and the discourses of modernity, using the example of St. James’s Park depicted in Juliusz Słowacki’s Kordian. The opening scene from Act II is placed in the context of the historical transformation of the park and against the backdrop of debates among urban reformers regarding the utility of parks (their role in promoting contact with nature and shaping religious and social attitudes). The article thus reveals Kordian’s historical and cultural (additionally also metaphysical) unawareness concerning the semantic richness of the space in which he embarks on his initiation journey throughout Europe. Consequently, this exposes the protagonist’s illusion concerning the possibility of returning to the state before industrialization, urbanization and the progressive democratization of society. Analysed in juxtaposition with the works of Pückler-Muskau and Byron, the scene demonstrates how Słowacki imbues Kordian with a naïve consciousness associated with the concept of rus in urbe and a return to the Garden of Eden, which are impossible to realise in the post-natural world, but only imitated in a city park in the capital of the industrial world.